2017
DOI: 10.1007/s40430-017-0897-3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of MHD three-dimensional Carreau nanoliquid flow over bidirectionally moving surface

Abstract: The present work has abundant applications in the branch of mechanical engineering. Heat and mass transport analysis is very important in the manufacturing of various mechanical systems like heat exchangers, domestic refrigerator, fuel cells, hybrid-powered engines and thermal management of vehicles. We explored the features of three-dimensional magnetohydrodynamic (MHD) flow and heat transport phenomenon of Carreau nanoliquid over a stretched sheet under the influence of thermal radiation. The system of ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 46 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…Considering the above suppositions, the consistent mass, momentum, energy, and conservation of nanoparticles volume fraction equations in a Cartesian coordinate system (x, y, z) as follow [34][35][36][37][38]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Considering the above suppositions, the consistent mass, momentum, energy, and conservation of nanoparticles volume fraction equations in a Cartesian coordinate system (x, y, z) as follow [34][35][36][37][38]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…Species concentration qualitatively follows the same behavior as that of temperature. Table 2 Comparison of various values of c with Hayat et al [36], Rudraswamy et al [37] and Ganesh et al [38] c Hayat et al [36] Rudraswamy et al [37] Ganesh et al [38] Present results Figures 5, 6 and 7 depict the deviations in velocity, temperature and concentration profiles for distinct values of 2 , and it is observed that the velocity increases with increasing 2 as it enhances the drag experienced by stretching plane. The profile of temperature and thermal boundary layer thickness is reducing objectives of 2 .…”
Section: Resultsmentioning
confidence: 95%
“…For mass, momentum and heat transport, non-homogeneous equilibrium models in nanofluids embody four equations with two components, as expressed by Buongiorno [12]. Some interesting results pertaining to the use of nanofluids can be found in [13][14][15][16]. Recently, insufficient expressive efforts for nonlinear thermal radiations have been observed in these investigations [17].…”
Section: Of 20mentioning
confidence: 99%